Association between First-Year Virological Response to Raltegravir and Long-Term Outcomes in Treatment-Experienced Patients with HIV-1 Infection. Issue 3 (April 2015) - Eron, Joseph J; Cooper, David A; Steigbigel, Roy T; Clotet, Bonaventura; Yeni, Patrick; Strohmaier, Kim M; Rodgers, Anthony J; Barnard, Richard J; Nguyen, Bach-Yen T; Teppler, Hedy; ,
Background: We explored the relationship between virological response in the first year of treatment and long-term outcomes in the BENCHMRK studies. Methods: Patients failing antiretroviral treatment with 3-class resistant HIV-1 received double-blinded raltegravir (or placebo) with optimized background therapy (OBT) until week 156, followed by open-label raltegravir with OBT up to week 240. In this exploratory analysis of patients randomized to raltegravir, virological response over weeks 16–48 was categorized as continuous suppression (CS; viral RNA [vRNA] always <50 copies/ml), low-level viraemia (LLV; vRNA always <400 copies/ml, >50 copies/ml at least once), or not suppressed (NS; vRNA >400 copies/ml at least once). The association between these first-year vRNA response categories and baseline factors was analysed with univariate and multi-variate models. Virological and immunological outcomes for years 2–5 were assessed by first-year vRNA response category (observed failure approach). Results: Baseline vRNA, baseline CD4 + T-cell count and rapid viral decay (vRNA <50 copies/ml between weeks 2–12) correlated with first-year vRNA response ( P <0.001); only rapid viral decay remained significant by multiple regression. Virological response rates were similar in the LLV and CS groups and lowest in the NS group. CD4 + T-cell count increased through week 240 in the CS and LLV groups. Time to loss of virological response (confirmed vRNA ≥400 copies/ml) through week 240 did not support as strong a difference between the LLV and CS groups (log-rank P =0.11) as previously reported through weeks 156 and 192 ( P <0.05). Conclusions: Treatment-experienced patients on a raltegravir-based regimen with early LLV may have long-term virological and immunological benefit when their therapy is maintained.